Peran Penyuluh Perikanan Dalam Membina Kelompok Pembudidaya Ikan (POKDAKAN) DI Kecamatan Balikpapan Timur Kota Balikpapan - Noor Fitriana Ananda; Helminuddin; Elly Purnamasari (2339-1324, 2023)
This study aimed to discover the role of Fishery extension Officers in Developing Fish Aquaculturer Groups (POKDAKAN) in East Balikpapan Sub-district, Balikpapan, and the obstacles faced by the fishery extension officers in performing their role to develop the fish Aquaculturer groups (POKDAKAN) in East Balikpapan Sub-district. The primary data collection was conducted in November 2021 in East Balikpapan Sub-district; the primary data using an interview was collected using the list of questions based on the study objective. The sampling method referred to the census method involving 56 fish aquaculturer groups as the respondent. The findings showed that the role of fishery extension officers as motivators and communicators was in the “Strongly Play a Role” category, while the role of fishery extension officers as facilitators, mediators, and organizers was in the “Play a Role” category. The overall fish aquaculturer groups’ perception of the role of fishery extension officers in East Balikpapan Sub-district was in the “Strongly Play a Role” category with an average score of 37.85 in the score range between 37.36 and 48.00. The obstacle faced by the fishery extension officers in developing fish aquaculturer groups was the difficulty in passing by the damaged access road to the location during the rainy season. Another obstacle was that the officers did not frequently receive information updates regarding the technology from the relevant institution/office.